Consentimento informado em tempos de pandemia : como a incerteza da ciência pode atender à necessidade de informações seguras por parte do paciente? - Azevedo, Geysa Adriana Soares (2022)
The Covid-19 Pandemic surprised by the rapid contagion between people and the way national and international institutions dealt with the problem. The medical crisis that followed this pandemic made it difficult to organize medical and health in the most different orders. One of the main consequences was the high impact of administering drugs of different species for the treatment of a disease of profound scientific uncertainty. The text that is presented understands that there is an ethical duty to pay attention and support to the most vulnerable people affected by the disease. Given this circumstance, the problem that guides this research is: should the question of the analysis of informed consent in the assessment of the physician's civil liability undergo some variation in the context of the use of off-label medicines in the Covid-19 pandemic? As a central hypothesis, it starts from the idea that if the new structures caused by the Covid-19 Pandemic are understood within a health crisis perspective, then informed consent is closely linked to the promotion of fundamental rights related to health, such as right to medical information, free personality development and autonomy. Faced with the problem outlined and the hypotheses raised, a legal-dogmatic method is used, associated with hypothetical-deductive reasoning, based on bibliographic and documentary research. In order to structure this research, it is necessary to reach a measure of analyzing how the principle of informed consent is presented as a fundamental instrument in the assessment of the physician's civil liability in the use of off-label medicines in the context of the Covid-19 pandemic. First, to investigate the concept, characteristics and historical evolution of informed consent, as well as its role in the pandemic context, based on the principle of human dignity and soon after, to categorize the elements and assumptions of informed consent and medical responsibility. Finally, medical civil liability and the duty of information to the patient in the Covid-19 pandemic are analyzed. It is understood that the Brazilian legal system, despite not expressly disciplining the use of off-label drugs, allows, from a systematic interpretation, to corroborate health resolutions that guide their prescription according to the fundamental social right to health and the right to science. Thus, off-label prescription should only occur when there is scientific evidence indicating that it is an apparently effective and beneficial therapy for the patient. In this way, the off-label use of hydroxychloroquine associated with azithromycin in the treatment of Covid-19 reached a short window of legality, determined by Didier Raoult's research and consequent releases for emergency use by regulatory agencies, ending with the publication of studies proving its ineffectiveness, and consequent revocation by the Food and Drug Administration, as well as the World Health Organization.